2023
DOI: 10.3390/ma16114089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stabilized Martensite on the Long-Term Performance of Superelastic NiTi Endodontic Files

Patricia Sánchez,
Benedetta Vidi,
Jesús Mena-Alvarez
et al.

Abstract: One of the most used rotary files in endodontics is NiTi files due to their superelastic properties. This property means that this instrument has extraordinary flexion that can adapt to large angles inside the tooth canals. However, these files lose their superelasticity and fracture during use. The aim of this work is to determine the cause of fracture of the endodontic rotary files. For this purpose, 30 NiTi F6 SkyTaper® files (Komet, Germany) were used. Their chemical composition was determined by X-ray mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…It should be noted that the properties of NiTi orthodontic wires may depend on various aspects; chief among them are consistent chemical composition [ 14 , 15 ], grain size [ 14 , 16 ], mechanical and thermal cycling [ 17 ], residual stresses [ 18 ], and whether the surface treatment of wires improves friction coefficients. In addition, possible heat treatments of wires for flexibility, loops, or soldering to obtain different forces in the molar or canine areas produce substantial changes in the transformation temperatures and, therefore, in the superelastic curves [ 18 , 19 ]. Numerous studies have demonstrated that changes in temperature cause precipitation of precipitates rich in nickel or titanium, depending on the chemical composition of the wire, lead to a loss of the superelastic properties, rendering the wires useless for orthodontic therapy [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the properties of NiTi orthodontic wires may depend on various aspects; chief among them are consistent chemical composition [ 14 , 15 ], grain size [ 14 , 16 ], mechanical and thermal cycling [ 17 ], residual stresses [ 18 ], and whether the surface treatment of wires improves friction coefficients. In addition, possible heat treatments of wires for flexibility, loops, or soldering to obtain different forces in the molar or canine areas produce substantial changes in the transformation temperatures and, therefore, in the superelastic curves [ 18 , 19 ]. Numerous studies have demonstrated that changes in temperature cause precipitation of precipitates rich in nickel or titanium, depending on the chemical composition of the wire, lead to a loss of the superelastic properties, rendering the wires useless for orthodontic therapy [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%